2009
DOI: 10.1534/genetics.109.107813
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Mitochondrial DNA Instability of Autosomal Dominant Forms of Progressive External Ophthalmoplegia-AssociatedANT1Mutations inPodospora anserina

Abstract: Maintenance and expression of mitochondrial DNA (mtDNA) are essential for the cell and the organism. In humans, several mutations in the adenine nucleotide translocase gene ANT1 are associated with multiple mtDNA deletions and autosomal dominant forms of progressive external ophthalmoplegia (adPEO). The mechanisms underlying the mtDNA instability are still obscure. A current hypothesis proposes that these pathogenic mutations primarily uncouple the mitochondrial inner membrane, which secondarily causes mtDNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
(73 reference statements)
3
7
0
Order By: Relevance
“…DCD is also suppressed by cycloheximide, an inhibitor of cytosolic protein synthesis, which further supports the model that reduced cytosolic protein synthesis suppresses mitochondrial degeneration and DCD [89]. In P. anserina , premature cell death and mtDNA instability induced by ANT1 mutations are suppressed by a mutation in the AS1 gene encoding a ribosomal protein [90]. …”
Section: Ant Mutations Induce Degenerative Cell Deathsupporting
confidence: 58%
See 1 more Smart Citation
“…DCD is also suppressed by cycloheximide, an inhibitor of cytosolic protein synthesis, which further supports the model that reduced cytosolic protein synthesis suppresses mitochondrial degeneration and DCD [89]. In P. anserina , premature cell death and mtDNA instability induced by ANT1 mutations are suppressed by a mutation in the AS1 gene encoding a ribosomal protein [90]. …”
Section: Ant Mutations Induce Degenerative Cell Deathsupporting
confidence: 58%
“…The global mitochondrial damage model is supported by another study from El-Khoury and Sainsard-Chanet using the filamentous fungi Podospora anserina as a model system [90]. The A114P, L98P, and V289M alleles were introduced into the P. anserina ANT1 ortholog, PaANT .…”
Section: The Proteostatic Stress Modelmentioning
confidence: 99%
“…Expression of mutant forms of ANT associated with adPEO reduces ATP/ADP transport [96], and leads to large-scale mtDNA deletions which are characteristic of the disease [97]. ANT deficiency also leads to dilated cardiomyopathy.…”
Section: Physiological and Pathological Roles Of Slc25 Carriersmentioning
confidence: 99%
“…We proposed that the mutant proteins may interfere with general mitochondrial biogenesis in addition to their effect on oxidative phosphorylation and mtDNA stability and that mtDNA instability likely arises as a secondary effect of mitochondrial damage. By using the filamentous fungus Podospora anserine as a model system, El-Khoury and Sainsard-Chanet (2009) also showed that expression of the adPEO-type Ant variants leads to severe mitochondrial damage, as manifested by low mitochondrial membrane potential. The mechanism by which the mutant Ant causes mitochondrial damage is unknown.…”
Section: Introductionmentioning
confidence: 98%